Impact of COVID-19 on Stock Market Return and Volatility: Case Study of Canada on a Provincial, Regional, and National Level - Kang, Yong Joo (Journal of Applied Business and Economics, 2022)
This paper examines the impact of COVID-19 related information measures on the S&P/TSX Composite Index return and volatility from a local market perspective. The analysis is conducted on a Canadian provincial, regional, and national level using various measures related to the COVID-19 coronavirus, such as the infectiousness of the virus, stringency of government policies, and market sentiment, to identify the main drivers of the Canadian stock market. Our empirical results show that the measures impacting stock market return and volatility differ, with return driven primarily by market sentiment, and volatility driven by the infectiousness of the virus. These results are counter to the commonly held belief of returns being driven by fundamental macroeconomic variables and volatility being driven by market sentiment. While a formal test to determine the cause of the results is not conducted, the results could have potentially been fueled by the irrational behavior of investors who were looking to cash out on riskier stock market investments or shift them to safe assets.